SAT0285 Application of Criteria for the Diagnosis of "Clinical Osteoporosis" in a Population of Postmenopausal Women from Emilia-Romagna Region. (9th June 2015) - Vukatana, G.; Fila, E.; Rossi, E.; Buffa, A.; Lumetti, F.; Bortoluzzi, A.; Cagnoni, C.; Falchetti, A.; Bonaccorsi, G.; Malavolta, N.; Mascia, M.T.
Abstract : Background: Postmenopausal osteoporosis (OP) and fragility fractures (FF) strongly impact individual life and socio-economical aspects. FRAX algorithm quantifies the absolute risk of fracture at 10 years and together the assessment of BMD is recommended to identify subjects at greatest risk allowing preventive and therapeutic strategies. Objectives: Recently, it has been suggested (1) to apply the clinical diagnosis of OP in presence of the following criteria: a) femoral or vertebral T-score ≤ -2.5; b) previous atraumatic hip fracture or vertebral, proximal humerus and wrist FF in osteopenia; c) significant 10 years high-risk fracture by FRAX. We used them in the data collected at ERGO (Emilia-Romagna Osteoporosis Group) Project to assess the prevalence of OP and identify subjects candidates for anti-fracture therapy in a sample of postmenopausal women (PMW). As part of the ERGO clinical audit, we evaluated the approach to OP by physicians from different medical specialties through data forms to evaluate the risk factors and calculate the FRAX score. Methods: Inclusion criteria for the screening of OP were according to 2012 NICE guidelines. We analysed clinical and instrumental data in PMW, aged 50-89 years, collected during 2013. Thus, 634 PMW, average age 71 years, median 72, 55% over 70 years, were studied. The age at menopause was 45-55 years. Only completed data records to accurately estimate FRAX, with or w/o BMD, were considered. The reasons for a specialist clinical evaluation were: a) OP 38%; b) different causes 60%; and c) different causes + OP 2%. Regarding the history of previous fractures: 4.3% of cases were at the hip, 21.5% at vertebrae and 14.4% at other sites. Results: The prevalence of DXA-assessed (DXAa) vertebral and femoral OP was of 38% and 29%, respectively. At the evaluation, 10.2% took anti-fracture therapy, but HRT; 19.5% were receiving only vitamin D and 13% only calcium supplementations. DXAa OP at one or more sites was found in 254 subjects (39.9%), 24 subjects (3.8%) had a previous femoral FF, and 36 subjects (5.7%), with vertebral or femoral osteopenia, had previous FF at spine, humerus or pelvis. FRAX scores at 10 years were significant in 305 individuals (63.1%). After subgrouping patients with DXAa OP (criterion a), and using filters for category (allowing in subsequent analysis to exclude subjects already covered by previous selection), the sample was stratified as it follows: a) previous hip fracture: 2.2%; b) significant FRAX results: 19.3%; c) previous vertebral, or other sites, fracture and vertebral or femoral osteopenia: 0.3%; d) clinical OP (criteria b and c) 21.8%; e) DXAa only OP (criterion a) 39.9%; and f) clinical OP (criteria a, b, c) 61.7%. Conclusions: The application of criteria for clinical diagnosis of OP in our PM and senile women, allowed an integrated, real-life, assessment of the fracture risk in subjects from heterogeneous clinical specialized areas. Approximately, 61% of the subjects were candidates to receive anti-fracture drug therapy. Our data confirm that the awareness of OP is still underestimated and, consequently, subjects at high risk for FF are still undertreated. References: Siris E. et al, Int Osteop, 2014. Disclosure of Interest: None declared